Constructed Spaces: Affordances and a Theology of the Built Environment in Christian Early Childhood Education - Hyde, Brendan (Religions, 2025)
Drawn from a wider study, the research reported here utilised a phenomenology of practice to investigate Australian early childhood teachers’ perceptions of constructed spaces that enhance the Christian education of children. The study was conceptually framed by the notions of constructed space, affordance theory and a theology of the built environment. Four participants were interviewed using Zoom, and their transcripts analysed using a phenomenological framework. The analysis indicated that the constructed space yielded five types of affordances—emotional space, embodied space, physical space, relational space and theological space. The findings suggest that it is the constructed environment of the early childhood centre itself that affords particular types of spaces, such as emotional space, embodies space and so on. The findings also indicate that it is the educator who makes the difference in seeing the possibility for and creating such spaces, and their intentionality in acting to create such spaces. While there are limitations to this study, including the small sample size, the findings nonetheless indicate the importance of the constructed space in enhancing the Christian education of young children in early childhood educational contexts.